Biomimetic synthesis of silver nanoparticles from Streptomyces atrovirens and their potential anticancer activity against human breast cancer cells. Issue 8 (11th September 2017) - Subbaiya, Ramasamy; Saravanan, Muthupandian; Priya, Andavar Raja; Shankar, Konathala Ravi; Selvam, Masilamani; Ovais, Muhammad; Balajee, Ramachandran; Barabadi, Hamed
Abstract : Silver nanoparticles (AgNPs) have been undeniable for its antimicrobial activity while its antitumour potential is still limited. Therefore, the present study focused on determining cytotoxic effects of AgNPs on Michigan cancer foundation‐7 (MCF‐7) breast cancer cells and its corresponding mechanism of cell death. Herein, the authors developed a bio‐reduction method for AgNPs synthesis using actinomycetes isolated from marine soil sample. The isolated strain was identified by 16s ribotyping method and it was found to be Streptomyces atrovirens . Furthermore, the synthesised AgNPs were characterised by various bio‐analytical techniques such as ultraviolet–visible spectrophotometer, atomic force microscopy, transmission electron microscopy, Fourier transform infra‐red spectroscopy, and X‐ray diffraction. Moreover, the results of 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay reveals 44.51 µg of AgNPs to have profound inhibition of cancer cell growth; furthermore, the inhibition of MCF‐7 breast cancer cell line was found to be dose dependent on treatment with AgNPs. Acridine orange and ethidium bromide double staining methods were performed for cell morphological analysis. The present results showed that biosynthesised AgNPs might be emerging alternative biomaterials for human breast cancer therapy.